İnsan hakları perspektifinden İran İslam Cumhuriyeti'nde kadın hakları - Moein, Yasamin (İstanbul Bilgi Üniversitesi, 2020)
ÖZET: İran günümüz kadın haklarının durumu, bir yandan yüksek eğitim düzeyleri ve düşük doğum oranları, diğer yandan kadınların çalışma hayatına ve siyasete düşük katılımları ile çelişkili görünmektedir. 1979 İran devrimi sonrası İranlı kadınların hakları sınırlandırıldı, evlerinde tutularak sosyal yaşamdan tecrit edildiler. Bu tezin amacı; kadın hakları, cinsiyet eşitliği, ayrımcılığın ve kadına yönelik şiddetin önlenmesi ile ilgili İran İslam Cumhuriyeti Anayasası'nda kabul edilen yükümlülükleri ve diğer yasal düzenlemeleri incelemektir. Bu tez karşılaştırmalı bir bakış açısıyla hem Pehlevi rejimi sırasında hem de devrim sonrası dönemde kadın haklarına odaklanmaktadır. Çalışma beş bölümden oluşmaktadır. Birinci bölümde İran İslam Cumhuriyeti'ndeki güç, hukuk ve kadın konuları irdelenecektir. İkinci bölümde İran medeni hukukunda şeriat, örf adet hukuku ele alınacaktır. İran toplumu erkek egemen bir ataerkil toplum olduğundan, üçüncü bölüm ataerkilliğe ve bunun kadınlar üzerindeki olumsuz etkilerine odaklanacaktır. İran'daki kadınlar, aile ve evlilik konuları dördüncü bölümde değerlendirilecektir. Son olarak, beşinci bölümde İran'daki insan hakları hukuku ve kadınların durumu incelenecektir. İran tarihi ve kültüründeki ataerkil yapı, dini (İslami) devlet politikası ve ideolojisi ve muhafazakâr toplum yapısı gibi pek çok faktör, kadınların bugünkü İran'daki statüsünü şekillendirmektedir. Artan küreselleşme süreci, kadın hakları konusunda farkındalığın artması, ulusüstü feminist aktivizmin yayılması, uydu televizyon, internet ve sosyal medya gibi yeni iletişim teknolojileri yeni bir yol açmıştır. Bu çalışmanın bulgularından, insan haklarının otoriteler tarafından bahşedilmediği, ancak halkın kendi çabalarıyla kazanılması gerektiği sonucuna varılabilir. İranlı kadınlar bu gerçeğin cesaret verici bir örneği olarak düşünülebilir.

ABSTRACT: In present day Iran women have a paradoxical status. Although they have a higher level of education and fewer children, their participation in the economic and political life of the country is considerably lower than in pre-revolutionary era. The Iranian revolution of 1979 has dealt a serious blow on the civil and democratic rights of women in the social, legal, economic and political spheres. There are relatively fewer employment opportunities for women in a gendered job market, and their participation in the political process is ideologically determined by the Islamic regime.Women are the main loser of the revolution, and their civil and democratic rights and liberties have been seriously curtailed in comparasion with the pre-revolutionary times. The objective of this thesis is to investigate the restrictions imposed on women by the Constitution law and other legal documents in the Islamic republic, and evaluate their consequences for women’s rights, gender equality, discrimnatory and exclusionary practices and violence against women. This investigation is conducted in a comparative framework with the rights and liberties enjoyed by the Iranian women under the monarchy. The thesis contains five chapters, plus an introduction and a concluding section. Chapter 1, examines the status of the women in the legal and political structures of the Islamic regime. Chapter 2, is evaluates the place of the Sharia and customary law in the construction of civil law. Chapter 3, deals with institution of patriachy and its adverse effects on the representation women and their staus in the legal system. Chapter 4, examines the status of women in marriage and family law. Chapter 5, focuses on the legal status women in Iran and the Human Righs Law. The concluding part argues that the staus of women in Iranian society is defined by the multiplicity of internal and external factors ranging from Patriachal discourses and practices, repressive state policies and authoritarian ideology on the one hand, to globalisation, feminism and discourses of consciousness raising and empowerment, modern electronic and digital communication, internet and social media on the other. It is thus contended Islamic regime will not grant human rights to its citizens willingly and that they cannot be gained without struggle. The struggle of the Iranian women in the past four decades presents a shining example.
Women's rights from the perspective of human rights in the Islamic Republic of Iran
Keywords: Gender Equality; Women’s Rights in Iran; Human Rights; Islamic Revolution; Iranian Women Movements; Cinsiyet Eşitliği; İran’da Kadın Hakları; İnsan Hakları Hukuku; İslami Devrim; İranlı Kadın Hareketleri